2020
DOI: 10.21123/bsj.2020.17.2.0426
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between LCS6 Variant in KRAS Gene with the Occurrence of Breast Tumors in Iraqi Women

Abstract: Breast cancer is the most commonly diagnosed cancer and remains one of the main reasons of cancer-related mortality in women worldwide. KRAS variant rs61764370 (T>G) is associated with an increased risk of occurrence of many cancers, Here The case-control study was accomplished on 135 women including 45 women with breast cancer patients, 45 women with benign breast lesions and 45 healthy women to analyze the association of KRAS variant rs (61764370 T>G) with breast cancer. LCS 6 variant in KRAS gene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…According to the results of chin et al (17), the prognostic role of LCS6 variants in KRAS 3'-UTR causes an increase in the expression of KRAS. In addition, (18) stated that LCS6 variants of the KRAS gene were statistically non-significant in women with breast tumours compared with healthy control. Therefore, there are no comparatively different levels of KRAS mRNA, which may also be due to the human mRNA being mostly targeted by several miRNAs at different target sites, which may enable recompensing of the loss of a single binding site (19).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of chin et al (17), the prognostic role of LCS6 variants in KRAS 3'-UTR causes an increase in the expression of KRAS. In addition, (18) stated that LCS6 variants of the KRAS gene were statistically non-significant in women with breast tumours compared with healthy control. Therefore, there are no comparatively different levels of KRAS mRNA, which may also be due to the human mRNA being mostly targeted by several miRNAs at different target sites, which may enable recompensing of the loss of a single binding site (19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the variants analyzed in this study are present in mature mRNA and may play an important role in gene expression regulation via interactions with miRNAs [10]. Several studies have shown the association between SNVs present in the 3 UTR region of the KRAS gene and various types of cancer, including breast cancer, Wilms tumors, colorectal cancer, and glioma, among others [11][12][13][14][15][16][17]. According to the NIH SNP database, SNV rs12587 is located at chr12:25205894 (GRCh38.p14) and represents T > G transversion, whereas rs8720 is located at chr12:25206009 (GRCh38.p13) and entails the transition T > C. On the one hand, SNV rs12587 has been associated with Wilms tumor [12] and glioma [18], but it has not been associated with CRC [13].…”
Section: Introductionmentioning
confidence: 99%